Individual and environmental risk factors for tuberculosis disease - Simangunsong, Pahala Maringan Jubel; Wau, Herbert; Rusanti, Rina (Jurnal Prima Medika Sains, 2023)
This study aimed to analyse the association of individual and environmental factors with tuberculosis infection. The cross-sectional study was conducted in Puskesmas Sering, located in Medan Tembung subdistrict, North Sumatra, in November 2022. A total of 56 people were sampled in this study. Data were collected directly from the subjects by interview using a questionnaire sheet distributed to the respondents. Chi-square test was used to determine the significance of risk factors with tuberculosis disease. The results of the study showed that the prevalence of tuberculosis was 73.21%. The Chi Square test showed that all the risk factors such as age (0.002), gender (0.006), smoking habit (0.009), population density (0.014) and environmental sanitation (0.002) were significantly associated with tuberculosis disease.